Development and fabrication of carbon nanotube (CNT) based pH sensor - Low, Foo Wah (School of Nanoelectronic Engineering, 2013)
The development, fabrication and characterization of single-walled carbon nanotubes (SWCNTs) based pH sensor using aligned SWCNT were reported. The SWCNT alignment is defined by a single carbon nanotube aligned between the fabricated electrodes. This research involves the study of SWCNTs dispersion, alignment of SWCNT between microgap electrodes and characterization on the effect of change in the pH level on the impedance, conductance and capacitance of the aligned SWCNT.